Developing speaking skill learning materials based on Natural Order Hypothesis - Setiawan, Arif; Pranowo, Dwiyanto Djoko (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2022)
The literature on the teaching of English at higher education in Indonesia reflects that both English and non-English departments pay equal attention to the four language skills, namely speaking, listening, reading, and writing. However, there are still issues in the teaching of speaking skills especially in the English instruction for the non-English majors. This research tried to solve the issues using interventions in the form of learning materials focused on speaking skills based on Natural Order Hypothesis by Brown (1973), Burt (1974, 1975), and Krashen (1982, 2009, 2013) as well as the lesson plans used in the teaching of English for non-English majors in a state university in Yogyakarta. The materials were validated by subject experts and a field trial involving participants of 30 non-English department students was conducted. The effectiveness of the materials was measured using a validated instrument that had been pilot-tested to 10 respondents of the same backgrounds as the participants of the field trial. The research instrument utilized Sugiyono's (2015) formula with the results showing a percentage of 86.37 out of a possible 100%, which means that the materials are in the category of